PENDAMPINGAN PEMBUATAN CLINICAL PATHWAY DALAM PENINGKATAN MUTU PELAYANAN KESEHATAN DI RSUD DR. SOEKARDJO KOTA TASIKMALAYA - Ida Sugiarti; Fadil Ahmad Junaedi (Universitas Bakti Tunas Husada, 2022)
Clinical pathways are used for quality and cost control in health services in hospitals. A clinical pathway is the main requirement for quality control and cost control, especially in cases that have the potential to spend large resources. Research shows that the application of clinical pathways can reduce the length of stay and hospital costs. The existence of clinical pathways in hospitals is sought to refer to the National Guidelines for Medical Services (PNPK). The existence of clinical pathways at dr. Soekardjo does not all meet these criteria. Community service activities are carried out referring to the lecturer roadmap that has been made. The purpose of the activity is to the availability of clinical pathway forms that can be used in hospitals as needed and the preparation of clinical pathways according to PNPK criteria. The method of activity is in the form of FGD and Assistance in making clinical pathways. The activity was carried out well and agreed on a form that refers to the standards of the Hospital Accreditation Committee. Mentoring activities involve all health workers as users, both doctors, nurses, pharmacists, nutritionists, and PMIK so that the results are expected to be by the needs of the hospital. The results of the activity are in the form of an agreement on the form used and the arrangement of 10 clinical pathways according to the needs of the hospital.